2021
DOI: 10.1007/s11756-021-00818-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tick microbiota vaccines: how can this actually work?

Abstract: The main importance of ticks resides in their ability to harbor and transmit microorganisms that cause disease to animals and humans. In addition to pathogens, ticks coexist and interact with symbionts, and commensal bacteria that together form an ecological unit, the tick holobiont. The holobiont is an additional organismal level on which natural selection operates. The components of the tick hologenome, composed of host and microbiome genomes, are complimentary. In agreement with this proposition, antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…The results suggest that host Abs bind and kill Escherichia-Shigella bacteria in the tick microbiome, a conclusion supported by two evidences: (i) a negative correlation between the levels of both anti-E. coli IgM and IgG and the relative abundance of Escherichia-Shigella in the tick microbiome and (ii) the binding of anti-E. coli IgM and IgG to E. coli ex vivo. Thus, anti-tick microbiota vaccines can be used to target specific taxa within the tick microbiota through host antibodies (59). We also showed that tick engorgement, microbiome bacterial diversity and microbial community structure can be disturbed by vaccination with E. coli highlighting the important role that keystone microbiota bacteria have in tick performance and microbiome.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The results suggest that host Abs bind and kill Escherichia-Shigella bacteria in the tick microbiome, a conclusion supported by two evidences: (i) a negative correlation between the levels of both anti-E. coli IgM and IgG and the relative abundance of Escherichia-Shigella in the tick microbiome and (ii) the binding of anti-E. coli IgM and IgG to E. coli ex vivo. Thus, anti-tick microbiota vaccines can be used to target specific taxa within the tick microbiota through host antibodies (59). We also showed that tick engorgement, microbiome bacterial diversity and microbial community structure can be disturbed by vaccination with E. coli highlighting the important role that keystone microbiota bacteria have in tick performance and microbiome.…”
Section: Discussionmentioning
confidence: 73%
“…Anti-tick microbiota vaccine can also be a powerful tool to evaluate the functional contribution of a specific taxon in tick microbiota on pathogen colonization and transmission. These results guide precise interventions for the control of tick infestations and pathogen infection/transmission (59).…”
Section: Discussionmentioning
confidence: 80%
“…There are no successful vaccines currently available for H. longicornis in cattle despite the isolation of several candidate antigens, including proteases, ferritins [73], and subolesin [74]. New technological advances in tick genomics, transcriptomics, and microbiome analysis offer the possibilities to target endosymbionts [75,76] or crucial genera in the gut microbiome of H. longicornis to reduce reproductive capability or to block the maturation and transmission of parasites [77,78]. Given that H. longicornis is parthenogenic, it is not known whether doxycycline or tetracycline targeting endosymbionts might compromise tick development and reproductive fitness [79].…”
Section: Vaccination Against H Longcornismentioning
confidence: 99%
“…Despite recent advances in vector microbiota research, the lack of tools for the precise and selective manipulation of the vector microbiome is currently a major limitation to achieving mechanistic insights into pathogen-microbiome interactions [ 20 , 24 ]. Recently, our team introduced anti-microbiota vaccines [ 25 ] as an innovative approach to vector microbiome manipulation [ 26 ] and the development of novel pathogen transmission-blocking vaccines [ 27 ]. Host immunization with keystone taxa (i.e.…”
Section: Introductionmentioning
confidence: 99%